A dimeric holin/antiholin complex controls lysis by phage T4 - Schwarzkopf, Jan Michel Frederik; Mehner-Breitfeld, Denise; Brüser, Thomas (Frontiers in Microbiology, 2024)
Lytic phages control the timepoint of host cell lysis by timing the holin-mediated release of cell walldegrading endolysins. In phage T4, the antiholin RI inhibits the holin T, thereby preventing early release of the T4 endolysin and lysis. The antiholin achieves lysis inhibition (LIN) in response to phage superinfections, thereby increasing the chance for lysis in an environment with lower phage concentration. The holin T consists of a small N-terminal cytoplasmic domain, a transmembranehelix, and a periplasmic C-terminal domain. The antiholin is targeted to the periplasm by a cleavable signal peptide. Recently, the periplasmic soluble domains of the holin and the antiholin were found to form T2/RI2 tetramers in crystals. To investigate the functional relevance of this complex, we reconstituted LIN in a phage-free system, using only RI, T, and the endolysin, and combined targeted mutagenesis with functional analyses. Inactivation of the RI signal peptide cleavage site did not abolish LIN, indicating that RI can function in a membrane-bound state, which argued against the tetramer. This led to analyzes showing that only one of the two T/RI interfaces in the tetramer is physiologically relevant, which is also the only interaction site predicted by AlphaFold2. Some holin mutations at this interaction site prevented lysis, suggesting that the RI interaction likely acts by blocking the holin oligomerization required for hole formation. We conclude that LIN is mediated by a dimeric T/RI complex that, unlike the tetramer, can be easily formed when both partners are membrane-anchored. N25A Interface 2 no no R61A Interface 2 no no R61Q Interface 2 no no N25A R61A Interface 2 no no K65A Interface 2 no no K65L Interface 2 no no A24P Signal cleavage site yes no V41A control yes no V41G control yes no